Influence of HIV virus in the hospital stay and the occurrence of postoperative complications classified according to the Clavien-Dindo classification and in comparison with the Charlson Comorbidity Index in patients subjected to urologic and general surgery operations. Our preliminary results - Dimitrios Dimitroulis (Archivio Italiano di Urologia e Andrologia, 2017)
Objectives: From the first time that human immunodeficiency virus (HIV) was discovered, till today both the quality of life and survival expectancy of HIV-infected patients have markedly improved. As the life expectancy of these patients increases due to the use of highly active anti-retroviral therapy (HAART) also increases the number of HIV-positive patient to be subjected to an operation. Different studies have examined the occurrence of complications in this particular group of patients and their possible susceptibility to infections or other complications that could lead to increased hospital stay, morbidity and mortality with controversial results. Material and methods: We retrospectively analyzed the data of 25 HIV-patients that were subjected to general surgery and urologic operations and we also examined in comparison with the Charlson score and their comorbidities the occurrence of complications and subsequently the possibility of an increase hospital stay due to their HIV infection. Alongside we classified their complications according to the Clavien-Dindo and compared these complications in relation to their Charlson score and CD4 count. Results: 10/25 (40%) of the population had prolonged hospital stay and from this population 6 (6/25) (24%) patients had less than 200 CD4 constituting the AIDS subpopulation. The decline of the CD4 count showed a tendency for the occurrence of a complication and comorbidities to HIV-positive patients seem to affect more the AIDS subpopulation. Conclusions: Although this is a small retrospective study, we tried to classify our complications according to the Clavien- Dindo classification and combine the classification to the age adjusted Charlson score index of comorbidities.